1987
DOI: 10.1038/326493a0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and rates of enamel growth in the molar teeth of early hominids

Abstract: A recent study of the surface manifestation of incremental lines associated with enamel formation suggested that the crowns of early hominid incisor teeth were formed more rapidly than those of modern humans. In the absence of comparative data, the authors were forced to assume that enamel increments in fossil teeth were similar to those in modern humans. We have used evidence from the fractured surfaces of molar teeth to deduce estimates for both long- and short-period incremental growth markers within enamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 12 publications
5
93
2
Order By: Relevance
“…Extant great ape cuspal enamel formation represents only approximately 15-20% of total crown formation time, compared to approximately 40% in A. turkanensis. The A. turkanensis ratio is similar to the pattern seen in Paranthropus robustus and P. nyanzae, while an even higher ratio is seen in G. freybergi and Paranthropus boisei, which have extremely thick enamel (Beynon and Wood, 1987;Grine and Martin, 1988;Beynon et al, 1998;Smith et al, 2001). Grine and Martin (1988) considered three variables that relate to enamel thickness: ameloblast secretion rate, the total period of secretion, and the number of cells that are active at any given time.…”
Section: Crown Formation Time and Patterns Of Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant great ape cuspal enamel formation represents only approximately 15-20% of total crown formation time, compared to approximately 40% in A. turkanensis. The A. turkanensis ratio is similar to the pattern seen in Paranthropus robustus and P. nyanzae, while an even higher ratio is seen in G. freybergi and Paranthropus boisei, which have extremely thick enamel (Beynon and Wood, 1987;Grine and Martin, 1988;Beynon et al, 1998;Smith et al, 2001). Grine and Martin (1988) considered three variables that relate to enamel thickness: ameloblast secretion rate, the total period of secretion, and the number of cells that are active at any given time.…”
Section: Crown Formation Time and Patterns Of Developmentmentioning
confidence: 99%
“…5 Dean et al (1993a). 6 Beynon and Wood (1987). These authors did not specify the tooth from which specific values were measured.…”
Section: Crown Formation Time and Patterns Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to a combination of more enamel secretion per day by ameloblasts and a faster rate of ameloblast activation. 96 We need more information before we can determine whether these differences are due to selection operating on life history, on diet, or on a combination of the two.…”
Section: Dental Ontogenymentioning
confidence: 99%
“…afarensis molar fragments (AL 333-52 and AL 336-1) at between 2.2 and 2.4 years. Beynon & Wood (1987) calculated a range of molar crown formation times of 2.12 -2.59 years in P. boisei, while Ramirez Rozzi (1993,1995) found ranges of 1.93-2.49 years for P. aethiopicus but a greater range for enamel formation times of P. boisei molars of all types (2.67 -3.43 years). In P. robustus from Kromdraai, Lacruz (2006) calculated protoconid formation times at between 1.98 and 2.38 years and metaconid time to be near identical (1.92 -2.37 years) but Lacruz et al (2006) reported protocone formation times in two Au.…”
Section: (B) Molar Initiation Timesmentioning
confidence: 99%